Institutional Investors and the Information Content of Earnings Announcements: The Case of Poland - Amir Tavakkol; Piotr Korczak (European University Viadrina, The Postgraduate Research Programme: Capital Markets and Finance in the Enlarged Europe, 2005)
This paper investigates the relationship between market reaction to earnings surprises and institutional concentration in the firm's shareholders base. We use data from the Polish stock market where pension funds form a homogenous and highly competitive investor class with an increasing share in the market capitalisation and trading volume. We find evidence that higher pension funds holdings in a company tend to reduce the magnitude of market reaction around public disclosures. We interpret these findings as an information advantage that funds have over individual investors, which may result from scale economies in gathering and processing public information, as well as from access to privileged information in the interim period. We also find that company mangers are selective as to the type of information they provide to the market prior to their scheduled disclosures.
Keywords: M41; G14; G23; 330; public disclosure; information advantage; institutional investors; Institutioneller Anleger; Publizitätspflicht; Gewinn; Informationswert; Börsenkurs; Insiderhandel; Polen